2011
DOI: 10.1007/s00268-011-1152-1
|View full text |Cite
|
Sign up to set email alerts
|

Teamwork and Team Decision‐making at Multidisciplinary Cancer Conferences: Barriers, Facilitators, and Opportunities for Improvement

Abstract: Results are consistent with previous research: Members of the MCC are positive about the benefits of MCCs, although improving the way MCCs work is a goal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
95
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 108 publications
(104 citation statements)
references
References 42 publications
(65 reference statements)
6
95
1
2
Order By: Relevance
“…The practice of some 'core' members of MDTs, meeting socially on a regular basis, or going on holiday together has been observed. The interpersonal MDT relations have not been a focus in our study, but as this research continues we believe that the dynamics among individuals in an MDT has a greater bearing on the success of an MDTM that we would have ascribed 5 years ago; a fact that appears validated in other work [27].…”
Section: Changed Function Of the Mdtmmentioning
confidence: 82%
See 2 more Smart Citations
“…The practice of some 'core' members of MDTs, meeting socially on a regular basis, or going on holiday together has been observed. The interpersonal MDT relations have not been a focus in our study, but as this research continues we believe that the dynamics among individuals in an MDT has a greater bearing on the success of an MDTM that we would have ascribed 5 years ago; a fact that appears validated in other work [27].…”
Section: Changed Function Of the Mdtmmentioning
confidence: 82%
“…Patients clearly benefit from being treated by a surgeon with a high workload [24], but the impact of the stress and emotional exhaustion identified in MDTs [25] has yet to be measured, and [26] suggests that quality assurance measures are needed. While several have sought to identify the factors that help MDTMs work better [27][28][29] a general formula for success remains elusive.…”
Section: Analysis Of the Effects Of Mdtmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, nurses are better placed than physicians at obtaining and making sense of information about patients' psychological and social circumstances as well as their beliefs about and preferences for treatment; information that is positively associated with reaching a decision. Thirdly, previous research has shown that information on patients' comorbidities is important for ensuring that MTB decisions are clinically appropriate, as failure to integrate such information could result in decisions that are at best not implementable, and at worst dangerous [8,[25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…In summary, the analysis of the survey reveals a strong consensus between MDT members from different tumour types, while also identifying areas that require a more tailored approach, such as the clinical decision-making process, and preparation for and organisation of MDT meetings [5]. In addition, in a systematic review on factors that affect the quality of clinical decision-making of MDTs, several factors have been identified: inclusion of time to prepare for MDTs into team-members' job plans, making teams and leadership skills training available to team-members, and systematic input from nursing personnel would address some of the current shortcomings [7,12].…”
mentioning
confidence: 99%